(3CQHYhf MOjkKG ef CQHYjf cJGHkG ef cJH GdMOjK dCQHYjf ef GdeMOKjfs - (3YHO Gddg Hf Ydj Hf YHO GdQMef ShjOGf GdOedjLj,J (B1234 (3g` s
(3ChdgG (B:s
(3fMeOc jG ef hUd ef GfbWY Gdjg hHYO ajbhd YHO Gddg Hf Ydi ShjOGf s
(3BNQgG (B:s
(3GdMHQ GHf YHGS bGd TgOJ eY QShd Gddg Udi Gddg Ydjg hSde jhe YjO aWQkG hCVMi adeG aQZ ef GdUdGI CbHd YdjfG HhLgg abGd CjgG GdfGS bO CUHJe NjQkG aef CMH Cf jfUQa adjfUQa hef CMH Cf jbje MJi jSeY GdNWHI adjbe GfJgi hGddg CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B14s
(3HgGfXGe GdJYbjHI MOjKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B107 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B89s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI HgG JdhjK s
Keywords: (3GdeLGejYs